1995
DOI: 10.7164/antibiotics.48.306
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Cell Candida albicans Assay for the Detection of Inhibitors towards Fungal Cell Wall Synthesis and Assembly.

Abstract: A whole-cell C. albicans screen was designed to identify novel inhibitors interacting with the synthesis, assembly and regulation of the fungal cell wall. C. albicans was grown in a paired broth assay in 96-well plates with natural product extracts or pure chemical compoundsin the presence and absence of the osmotic stabilizer, sorbitol. Growthwas visually examinedover a 7-day period and scored into different growth categories. Positives from the sorbitol rescue were then examined under the microscope for morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 23 publications
1
136
1
3
Order By: Relevance
“…However, its growth will still be possible if sorbitol is supplemented. The inhibitors of the fungal cell wall could be identified when the MIC values obtained with sorbitol are higher than the ones in its absence after seven days of incubation (Frost et al, 1995). In the present assays, MIC of the ellagic acid against Saccharomyces cerevisiae was raised from 62 to 250 µg/mL in the presence of sorbitol 0.8 M, suggesting that the ellagic acid would act modifying the fungal cell wall, while the MIC of the amphotericin B was not modified, as expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its growth will still be possible if sorbitol is supplemented. The inhibitors of the fungal cell wall could be identified when the MIC values obtained with sorbitol are higher than the ones in its absence after seven days of incubation (Frost et al, 1995). In the present assays, MIC of the ellagic acid against Saccharomyces cerevisiae was raised from 62 to 250 µg/mL in the presence of sorbitol 0.8 M, suggesting that the ellagic acid would act modifying the fungal cell wall, while the MIC of the amphotericin B was not modified, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Sorbitol was added to the culture medium to give a final concentration of 0.8 M. Following incubation at 25 ºC, the plates were read at 48 h and after seven days (Frost et al, 1995). This assay was carried out in duplicate.…”
Section: Sorbitol Assaymentioning
confidence: 99%
“…Damage to essential cell wall components by antifungal agents will lyse cells in the absence of an osmo-protectant, but cells will continue to growth if a suitable stabilizer is present in the medium. Reiss et al (1992) and Frost et al (1995) found that antifungal-treated fungi were viable if broth cultures were protected with sorbitol, but lysed if plated out on agar without osmotic support. According to these authors, assays of osmotic stability have been applied in fungi for assessing the mode of action of classical or emerging antibiotics.…”
Section: Candida and Criptococcus Genus Are Known As The Yeasts Most mentioning
confidence: 99%
“…Control flasks of SB without sorbitol (standard media) were tested in the same manner. Based on the ability of sorbitol to act as an osmotic protector of fungi cell wall, the higher MIC values observed in the media with added sorbitol compared to the standard media implicated the cell wall as one of the possible cell targets of the essential oils (Frost et al, 1995).…”
Section: Sorbitol Assaymentioning
confidence: 99%
See 1 more Smart Citation